Insights and interventions for improving cultural humility towards Asian American, Native Hawaiian and Pacific Islander populations in medical curricula: a qualitative case study - Sandra Kong; Nathan Irvin; Connie Cai; Carolyn Im; Ethan Mondell; Thomas K Le; Shari M Lawson (BMJ Open)
Objectives The Asian American, Native Hawaiian and Pacific Islander (AANHPI) community is the fastest-growing racial/ethnic population in the USA. Previous research identified that medical students perceived a lack of exposure to AANHPI patients and topics in medical school curricula; however, there remains a lack of potential interventions to address this need. The goal of our study is to present a case study for identifying interventions in medical school curricula that improve cultural humility-based training for providing medical care for AANHPI populations.Design In this qualitative study, authors conducted four virtual focus groups with 15 medical students at a single institution to identify curricular interventions. The authors then conducted virtual semistructured interviews with eight medical educators one-on-one to explore the feasibility of the proposed interventions. Data were analysed using qualitative thematic analysis, and analysis was performed with ATLAS.ti.Setting Medical students and medical educators based at medical institutions in the USA.Participants 15 medical students and eight medical educators participated in the study.Results All medical students (n=15) and educators (n=8) noted that there is limited engagement of AANHPI communities in current medical curricula and limited curricular components that address the diversity within the AANHPI umbrella. Medical student focus groups identified three interventions to improve cultural humility-based training for treating AANHPI patients: reflection spaces, community engagement and clinical training on documenting cultural needs. Educators supported the feasibility and importance of these interventions to prepare students to work with not only AANHPI patients but also with patients of other diverse backgrounds.Conclusion AANHPIs represent a heterogeneous population consisting of unique cultural heritages. Our research demonstrates the importance of highlighting this community in cultural humility curricula to provide an example of how to consider and appreciate diversity in patient populations. In this paper, we present student and medical educator-supported curricular interventions that not only increase awareness of issues impacting AANHPI communities, but also emphasise building skills of self-reflection, lifelong learning and empathy that are applicable to patients of all backgrounds.